2019
DOI: 10.1038/s41598-019-52309-z
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Multi-target Inhibitor of angiotensin type 1 receptor and neprilysin inhibitors from Traditional Chinese Medicine

Abstract: Angiotensin II type-1 receptor–neprilysin inhibitor (ARNi) is consisted of Angiotensin II type-1 receptor (AT1) antagonist and neprilysin (NEP) inhibitor, which could simultaneously increase the vasodilators of the natriuretic peptides and antagonize vasoconstrictors of Ang II. ARNi has been proved a superior effect and lower risks of death on chronic heart failure (CHF) and hypertension. In this paper, ARNi from Traditional Chinese Medicines (TCM) was discovered based on target combination of AT1 and NEP by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The large size and shape of the binding site pose challenges for molecular docking on targets. In cACE and NEP molecular docking calculations, constraints are applied to obtain reliable orientations of ligands, including hydrogen bonds with His353 and/or His513 (cACE) and His711 (NEP) along with metal-chelator interactions 43 , 80 . The study found that native ligands in protein structure are maximally superimposed with co-crystallized ligands, confirming the docking protocol's agreement with previous work and confirming the interaction of native ligands(Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large size and shape of the binding site pose challenges for molecular docking on targets. In cACE and NEP molecular docking calculations, constraints are applied to obtain reliable orientations of ligands, including hydrogen bonds with His353 and/or His513 (cACE) and His711 (NEP) along with metal-chelator interactions 43 , 80 . The study found that native ligands in protein structure are maximally superimposed with co-crystallized ligands, confirming the docking protocol's agreement with previous work and confirming the interaction of native ligands(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advancements in the pharmaceutical industry, such as the development of a Losartan and metabolite co-drug with NEP inhibitors, demonstrate innovative approaches in drug discovery 41 . The discovery of orally active TD-0212 and Gyrophoric acid further emphasizes the necessity of dual AT1/NEP inhibition with potentially lower angioedema risk 42 , 43 . Omapatrilat and LCZ696 (Entresto®) are molecules discovered to target the renin–angiotensin–aldosterone system and neprilysin together 44 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Gyrophoric acid has been shown to have antihypertensive properties by acting as an angiotensin II type-1 receptor (AT1) antagonist by interacting with residues ARG167, TRP84, and VAL108 [ 123 ]. Moreover, gyrophoric acid has been identified as a non-competitive PTP1B inhibitor, with an IC 50 value of 3.6 μM, making it a drug candidate for type 2 diabetes and obesity [ 99 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
“…Other potential therapeutic effects of GA include cardiovascular action as a direct angiotensin II type-1 receptor antagonist (IC 50 of 29.76 µM) ( Huo et al., 2019 ), DNA interaction as a potential DNA-binding compound ( Plsíkova et al., 2014 ), and anti-diabetic activity through antiglycation and anti-urease activity ( Seo et al., 2009 ; Choudhary et al., 2011 ). There is also evidence that TE, the di-methylated analog of GA, may prevent Alzheimer’s disease.…”
Section: Pharmacological Importance Of Tridepsidesmentioning
confidence: 99%